Geometric Modeling and visualization of moving objects on a digital map - Kilimci, Perihan; Kalipsiz, Oya (IEEE COMPUTER SOC, 2007)
In order to model geographic space, we should consider obviously anything qualifies that might appear on a paper map for example, states, cities, mountains, rivers, highway networks, hospitals, police stations etc. These varied entities can be modeled by using geometric modeling concepts. In many internet applications and Geographical Information Systems (GIS) digital maps are used to indicate locations of interested static or moving objects which change their futures in spatial and temporal domain. In this paper, we visualized a spatial map which stores its data according to geometric modeling concepts and retrieves its data from database. Then, we simulated moving objects on a digital map according to predefined scenario.
Keywords: geometric modeling; moving objects databases; Computer Science; Engineering